Knowledge of Islamic medical practice among nursing and medical students in Kuantan, Pahang. - Mohd Arifin, Siti Roshaidai; Othman, Azimah; Daud, Normadiah (2021)
Islamic medical practice (IMP) includes spirituality in delivering healthcare services. Current studies on IMP focus on healthcare professionals with less attention given to the nursing and medical students. The objective of this study was to assess the level of knowledge of IMP among nursing and medical students. This descriptive cross-sectional study was conducted on 190 undergraduate nursing and medical students in Pahang, Malaysia. Most participants had a good level of knowledge on IMP (n=190, 70.5%). There was a significance association between the level of knowledge of Rukhsah Solah with the courses, training experience, and current year of study indicating p-value of 0.025, 0.006, and 0.003 respectively. This study indicates that the students have a good level of knowledge regarding IMP and a moderate level of Rukhsah Solah. Guidelines and protocols in IMP should be delivered to the nursing and medical students prior to their graduation to facilitate the sustainability of such practice.